PWE-187 Ethanol and Taurolidine Line Locks for the Reduction and Treatment of Catheter Related Blood Stream Infections in Paediatric Intestinal Failure: A Systematic Review. (4th June 2013) - Tayler, R; Barclay, A; Henderson, P; Wilson, D C
Abstract : Introduction: Paediatric intestinal failure (PIF) patients are often dependent on home parental nutrition (HPN) nd rely upon a central venous catheter (CVC) for its administration. There is a significant risk of catheter-related blood stream infections (CRBSI) with associated morbidity and mortality. Studies have suggested that the use of specialist line locks with ethanol or taurolidine may significantly reduce CRSBI for PIF. Our aim was systematically review the evidence for effectiveness of ethanol and taurolidine line locks in the prevention or treatment of CRBSI in PIF. Methods: Systematic retrieval of data from studies of PIF (PN > 28 days, age < 18yr). Outcome measures were the reduction in rates of CRBIS or eradication of CRBSI. Electronic searches of the Cochrane Library, MEDLINE (1946 –Jan 2013) and PUBMED (to Jan 2013) were made using keyword and MeSH terms 'Intestinal failure' 'child' 'ethanol locks' and 'taurolidine locks'. Hand searches of meetings of relevance and personal collections were also perfomed. Two authors independantly assessed the level of evidence (EL) using SIGN (Scottish Intercollegiate Guidelines Network) methodology (http.//www.sign.ac.uk). CRBSI rates were expressed as per 1000CVC days. Results: The search strategy yielded 3142967 hits. Combination searches using 'IF' and 'Child' reduced this to 2993. 14 studies were read in detail; 5 were excluded due to containing purely adult data or where data on PIF could not be analysed seperately. Nine studies were included in our review, 5 of CRBSI prevention and 4 of CRSBI treatment. 8 studies used ethanol alone and 1 reported taurolidine use (Table ). 4 studies reported success in prevention of recurrent line sepsis. 2 thrombotic episodes were reported. Conclusion: The data for the use of ethanol line locks are limited of poor methodoligical quality and of lower EL (there are no RCT's or well designed cohort studies). However ethanol locks appear to be an effective therapy in CRBSI prevention and treatment. With only 1 study of taurolidine locks no comparison can be made with ethanol locks. Future well designed studies are warranted to compare these two treatments. Disclosure of Interest: None Declared.